Deuterated Covalent Organic Frameworks with Significantly Enhanced Luminescence. (18th August 2021) - Yuan, Mengjia; Ma, Fuyin; Dai, Xing; Chen, Lixi; Zhai, Fuwan; He, Linwei; Zhang, Mingxing; Chen, Junchang; Shu, Jie; Wang, Xiaomei; Wang, Xia; Zhang, Yugang; et al.
Abstract: Luminescent covalent organic frameworks (COFs) find promising applications in chemical sensing, photocatalysis, and optoelectronic devices, however, the majority of COFs are non or weakly emissive owing to the aggregation‐caused quenching (ACQ) or the molecular thermal motion‐based energy dissipation. Here, we report a previously unperceived approach to improve luminescence performance of COFs by introducing isotope effect, which is achieved through substitution of hydrogen from high‐frequency oscillators X‐H (X=O, N, C) by heavier isotope deuterium. Combining the "bottom‐up" and in situ deuteration methods generates the first deuterated COF, which exhibits an impressively 19‐fold enhancement in quantum yield over that of the non‐deuterated counterpart. These results are interpreted by theoretical calculations as the consequence of slower C/N‐D and OD⋅⋅⋅O vibrations that impede the nonradiative deactivation process. The proposed strategy is proved applicable to many other types of emissive COFs. Abstract : A new approach to improve luminescence performance of covalent organic frameworks (COFs) is demonstrated by introducing an isotope effect, which is achieved through substitution of hydrogen in high‐frequency oscillators X‐H (X=O, N, C) by the heavier isotope deuterium. The first deuterated COF exhibits a 19‐fold enhancement in quantum yield over the non‐deuterated counterpart.